Analisis Faktor Spesifik Bank dan Corporate Governance terhadap Financial Sustainability BUS di Indonesia - Yuri Almaida; Ruhadi Ruhadi; Tjetjep Djuwarsa (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The background of research was implementation of financial sustainability on Sharia Commercial Banks in Indonesia not optimal since rules Number 51/POJK.03/2017 was published. The objective of research to test the influence of bank-specific factors proxied by CAR, FDR, NPF, BOPO, ROA and corporate governance measured by the number of sharia supervisory board meetings on financial sustainability proxied by Financial Sustainability Ratio (FSR). This research use explanatory quantitative approach. The result indicate that CAR has a significant influence in the same direction on FSR. FDR, BOPO and number of sharia supervisory board meetings have significant influence with the opposite direction on FSR. However, NPF and ROA didn’t have significant influence on FSR. Then, the average of financial sustainability on Sharia Commercial Banks in Indonesia has fulfilled the ideal standard by The World Bank with an FSR average value is 126.91%.